2016
DOI: 10.1002/cjce.22562
|View full text |Cite
|
Sign up to set email alerts
|

Combustion characteristics of ultrafine gasified semi‐char in circulating fluidized bed

Abstract: Coal fluidized bed gasification generates large amounts of semi‐char, which has a high carbon content. Effectively re‐burning semi‐char has become a promising way to improve overall conversion efficiency of coal gasification and use the residue carbon in the semi‐char. However, due to the ultrafine particle size (mean particle size ≈ tens of microns), nearly zero volatile content, and the graphitization structure of the semi‐char, the fluidization and combustion organization of semi‐char in a circulating fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The keywords in the second and third most cited articles (“Alkanethiolate Gold Cluster Molecules with Core Diameters from 1.5 to 5.2 nm: Core and Monolayer Properties as a Function of Core Size” and “Chemical Oxidation of Multiwalled Carbon Nanotubes”) touch on the red cluster: nanoparticles and nanotubes . In the seven articles published by The Canadian Journal of Chemical Engineering in 2016 and 2017 researchers grafted poly(methyl methacrylate) from the surface of CNCs using aqueous, one‐pot, free radical polymerization (yellow and blue clusters); evaluated thermal behaviour of ground pine chip particles and ground pine pellet particles (yellow cluster); synthesized NiFe 2 O 4 spinel in solid state (green cluster); tested the combustion characteristics and activation energy of the semi‐char from an industrial circulating fluidized bed (yellow cluster); monitored effects of NiO nanosorbants on adsorption and post‐adsorption catalytic thermo‐oxidative decomposition of vacuum residue asphaltenes (green and magenta clusters); evaluated the fuel properties and the reaction characteristics of two different oil shales and sub‐bituminous coal by non‐isothermal thermogravimetric analysis (yellow and green cluster); and analyzed the reaction model and dynamic reaction characteristics of limestone thermogravimetrically (yellow cluster) …”
Section: Applicationsmentioning
confidence: 99%
“…The keywords in the second and third most cited articles (“Alkanethiolate Gold Cluster Molecules with Core Diameters from 1.5 to 5.2 nm: Core and Monolayer Properties as a Function of Core Size” and “Chemical Oxidation of Multiwalled Carbon Nanotubes”) touch on the red cluster: nanoparticles and nanotubes . In the seven articles published by The Canadian Journal of Chemical Engineering in 2016 and 2017 researchers grafted poly(methyl methacrylate) from the surface of CNCs using aqueous, one‐pot, free radical polymerization (yellow and blue clusters); evaluated thermal behaviour of ground pine chip particles and ground pine pellet particles (yellow cluster); synthesized NiFe 2 O 4 spinel in solid state (green cluster); tested the combustion characteristics and activation energy of the semi‐char from an industrial circulating fluidized bed (yellow cluster); monitored effects of NiO nanosorbants on adsorption and post‐adsorption catalytic thermo‐oxidative decomposition of vacuum residue asphaltenes (green and magenta clusters); evaluated the fuel properties and the reaction characteristics of two different oil shales and sub‐bituminous coal by non‐isothermal thermogravimetric analysis (yellow and green cluster); and analyzed the reaction model and dynamic reaction characteristics of limestone thermogravimetrically (yellow cluster) …”
Section: Applicationsmentioning
confidence: 99%
“…4−7 Hence, some solutions have been proposed to realize the efficient utilization of such low-volatile fuels by combustion or co-combustion of semicokes. Some scholars have indicated that semi-coke could be burned in a circulating fluidized bed boiler, 8,9 and other researchers have put forward that semi-coke could be preheated before burning in a boiler. 10−12 However, new equipment and/or much reconstruction are necessary for the boiler to fire semi-cokes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pyrolyzed and gasified semi-cokes usually have ultra-low volatile content, with high NO x emission and poor combustion performance during combustion. Hence, some solutions have been proposed to realize the efficient utilization of such low-volatile fuels by combustion or co-combustion of semi-cokes. Some scholars have indicated that semi-coke could be burned in a circulating fluidized bed boiler, , and other researchers have put forward that semi-coke could be preheated before burning in a boiler. However, new equipment and/or much reconstruction are necessary for the boiler to fire semi-cokes. Besides, the strategy of cofiring gasified and pyrolyzed semi-cokes with bituminous coal in a pulverized coal furnace of the power plant is a promising approach to efficiently and cleanly consume these carbon-based solid fuels with ultra-low volatiles in a large scale. , The pulverized-coal boiler has accounted for the largest proportion in China, and only limited equipment needs to be upgraded for co-combustion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations